The impact and policy relevance of street lighting for crime prevention: a systematic review based on a half-century of evaluation research - Welsh, Brandon (Criminology & public policy, 2022)
Research Summary This article reports on an updated systematic review and meta-analysis of the effects of street lighting interventions on crime in public places. Following Campbell Collaboration guidelines, it uses robust criteria for inclusion of studies, comprehensive search strategies to identify eligible studies, a detailed protocol for coding key study characteristics, and rigorous methods for analyzing studies. A total of 21 studies met the inclusion criteria, originating in four countries (United States, United Kingdom, Brazil, and South Korea) and covering almost 50 years (1974-2021). The review finds that street lighting interventions are associated with a significant desirable effect on total crime (14% reduction in treatment areas compared with comparable control areas); desirable effects are greater in studies that measured both night and day crimes than in studies that only measured night crimes; and street lighting is followed by a significant reduction in property crimes, but not in violent crimes. Policy Implications Compared to past years, it would seem that an even stronger case can be made today for street lighting interventions to be part of crime-prevention policy. A larger body of high-quality evaluation research, implemented in a range of high-crime public places, some evidence of value for money, and a continued desirable impact on crime, especially property crime, all point to the policy relevance of street lighting interventions.